2015
DOI: 10.3389/fneur.2015.00158
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Cortical Network Activity in vitro and Promotion of GABAergic Neurogenesis by Stimulation with an Electromagnetic Field with a 150 MHz Carrier Wave Pulsed with an Alternating 10 and 16 Hz Modulation

Abstract: In recent years, various stimuli were identified capable of enhancing neurogenesis, a process which is dysfunctional in the senescent brain and in neurodegenerative and certain neuropsychiatric diseases. Applications of electromagnetic fields to brain tissue have been shown to affect cellular properties and their importance for therapies in medicine is recognized. In this study, differentiating murine cortical networks on multiwell microelectrode arrays were repeatedly exposed to an extremely low-electromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 67 publications
1
16
0
1
Order By: Relevance
“…This neuron/glia ratio of ~0.25 differs from the reported neuron/glia ratio of ~0.8 in mouse frontal cortex in vivo [ 33 ]. On the other hand, we have previously determined that approximately 20% of the neurons in these cultures are GABAergic neurons, which is in excellent agreement with ratio of GABAergic neurons (relative to total number of neurons) in mouse frontal cortex in vivo [ 30 , 34 ]. In the present study, we investigated the composition of the cortical networks and the nature and degree of synapse formation in them by means of immunocytochemistry using antibodies targeting synapsin-1, β3-tubulin and Hoechst-Bisbenzimid as markers for synaptic punctae, neurons and nuclei, respectively (n = 6).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…This neuron/glia ratio of ~0.25 differs from the reported neuron/glia ratio of ~0.8 in mouse frontal cortex in vivo [ 33 ]. On the other hand, we have previously determined that approximately 20% of the neurons in these cultures are GABAergic neurons, which is in excellent agreement with ratio of GABAergic neurons (relative to total number of neurons) in mouse frontal cortex in vivo [ 30 , 34 ]. In the present study, we investigated the composition of the cortical networks and the nature and degree of synapse formation in them by means of immunocytochemistry using antibodies targeting synapsin-1, β3-tubulin and Hoechst-Bisbenzimid as markers for synaptic punctae, neurons and nuclei, respectively (n = 6).…”
Section: Resultssupporting
confidence: 78%
“…As mentioned in section 2.2, the primary neurons were used for the MEA recordings between 28 and 35 days in vitro . Due to the serum used in the culture medium glia survival is supported in these cultures, and mainly because of proliferation of glia during the first 4 days after plating these neuron-glia co-cultures thus consist of approximately 20% neurons and 80% astrocytes including 1% microglia [ 30 ]. This neuron/glia ratio of ~0.25 differs from the reported neuron/glia ratio of ~0.8 in mouse frontal cortex in vivo [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Driving gamma oscillations using tACS modulates inhibition in the human motor cortex (Nowak et al 2017 ). Similarly, studies with rodents have shown that exposure to an extremely low-electromagnetic field (ELEMF) with alternating 10 and 16 Hz frequencies increased and intensified the burst structure in rodent’s cortical in vitro networks, as well as increasing the population of GABAergic neurons (Gramowski-Voss et al 2015 ). We also suggest that the net increase in inhibition in the motor cortex of the old group due to the stimulation was responsible for the lower facilitation of MEP amplitudes in the single-pulse TMS paradigm, the MEP recruitment in the I / O curve and possibly the ICF, which remained unchanged after stimulation in the old group.…”
Section: Discussionmentioning
confidence: 97%
“…К сожалению, в нейронауки и биоакустику данные разработки в тот период практически не поступают. Редкие исключения (например, работы по усилению волновой активности кортикальных нейросетей и их морфогенеза in vitro при стимуляции отдельными частотами (например, 150 МГц несущей при подаче пакетов сигналов с частотой 10-16 Гц) [97] только подтверждают правило, так как нейроэлектрофизиологические частоты не лежат в этом диапазоне несущей, а воздействие явно имеет физико-химический характер, а не модулирует активность нейросетей.…”
Section: разработки в области анализа несущей и модуляции на нейunclassified